2000
DOI: 10.1590/s0001-37652000000400006
|View full text |Cite
|
Sign up to set email alerts
|

Carbon isotope fluctuations in Precambrian carbonate sequences of several localities in Brazil

Abstract: Carbon isotope fluctuations in Precambrian sedimentary carbonates between 2.8 Ga and 0.60 Ga in Brazil are examined in this study. The carbonate facies of the BIF of the 2. On the light of the C isotope data discussed in this study, it seems that δ 13 C fluctuations in Paleoproterozoic carbonates in Brazil are within the range found globally for metasedimentary carbonates of this age. Carbon isotope data proved to be very useful in establishing relative chronology of Neoproterozoic carbonate formations for whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
7

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 28 publications
0
19
0
7
Order By: Relevance
“…2.2 Á/2.1 Ga (Karhu, 1993). Globally, Paleoproterozoic carbonate units correlative with the Nash Fork Formation based on similar carbon isotope systematics are also known, as discussed above from South Africa (Master et al, 1993;Buick et al, 1998;Swart, 1999;Bekker et al, 2001a) as well as Gabon (Gauthier-Lafaye and Weber, 1989), Zimbabwe (Bekker et al, 2001b), Australia (Lindsay and Brasier, 2002), India (Sreenivas et al, 2001), Scotland (Baker and Fallick, 1989a), Brazil (Sial et al, 2000), Russia (Akhmedov et al, 1996), and North America (Melezhik et al, 1997a;Bekker, 1998;Hofmann and Davidson, 1998).…”
Section: Implications For Global Correlationmentioning
confidence: 72%
“…2.2 Á/2.1 Ga (Karhu, 1993). Globally, Paleoproterozoic carbonate units correlative with the Nash Fork Formation based on similar carbon isotope systematics are also known, as discussed above from South Africa (Master et al, 1993;Buick et al, 1998;Swart, 1999;Bekker et al, 2001a) as well as Gabon (Gauthier-Lafaye and Weber, 1989), Zimbabwe (Bekker et al, 2001b), Australia (Lindsay and Brasier, 2002), India (Sreenivas et al, 2001), Scotland (Baker and Fallick, 1989a), Brazil (Sial et al, 2000), Russia (Akhmedov et al, 1996), and North America (Melezhik et al, 1997a;Bekker, 1998;Hofmann and Davidson, 1998).…”
Section: Implications For Global Correlationmentioning
confidence: 72%
“…This Domain is characterized by graben and horst structures controlled by NE-trending shear zones, and is bounded to the northeast by the Transbrasiliano Lineament, which separates it from the Ceará Central Domain (Caby et al 1991, Santos et al 2008. The age of the carbonate rocks of the Frecheirinha Formation is poorly constrained by C− and Sr-chemostratigraphy and radiometric ages as late Neoproterozoic (Sial et al 2000, Chiglino 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Zaine (1991) has measured C and O isotope ratios in carbonates of the Tamengo Formation, Corumbá Group, and Boggiani et al (1996) have identified an upper Ediacaran positive δ 13 C excursion, associated to the occurrence of Cloudina, which was correlated with the Arroyo del Soldado Group in Uruguay (Gaucher 1999). These studies were followed by systematic chemostratigraphic investigations on the Bambui, Una and Araras groups (Misi & Veizer 1998;Sial et al 2000;Santos et al 2000;Nogueira et al 2003;Alvarenga et al 2004;Misi et al, 2007). Sial et al (2000), Bekker et al (2003), and Maheshwari et al (2010) confirmed the record of the Lomagundi C isotope excursion in South America (Iron Quadrangle in Minas Gerais and Paso Severino Formation in Uruguay).…”
mentioning
confidence: 76%
“…These studies were followed by systematic chemostratigraphic investigations on the Bambui, Una and Araras groups (Misi & Veizer 1998;Sial et al 2000;Santos et al 2000;Nogueira et al 2003;Alvarenga et al 2004;Misi et al, 2007). Sial et al (2000), Bekker et al (2003), and Maheshwari et al (2010) confirmed the record of the Lomagundi C isotope excursion in South America (Iron Quadrangle in Minas Gerais and Paso Severino Formation in Uruguay). Sial et al (2008) reported, for the first time in South America, the positive carbon isotope excursion (SPICE) from the Steptoean at the Argentine Precordillera and recognized a Sunwaptan negative carbon isotope excursion (SNICE).…”
mentioning
confidence: 76%
See 1 more Smart Citation